THE EFFECTS OF TANNIN AND THERMAL TREATMENT ON PHYSICAL AND MECHANICAL PROPERTIES OF LAMINATED CHESTNUT WOOD COMPOSITES - Gunduz, Gokhan; Aydemir, Deniz; Onat, Saadettin Murat; Akgun, Kemal; Onat, Saadettin Murat; Aydemir, Deniz (North Carolina State Univ Dept Wood & Paper Sci, 2011)
The aim of this study was to investigate the effects of tannin and thermal treatment on physical properties such as dimensional stability and moisture content (%), as well as mechanical properties such as bending strength, modulus of elasticity, and compression strength of laminated chestnut wood composites, which are used commonly for shipboard construction in Turkey. The chestnut wood used in boat construction is usually exposed to several treatments in order to achieve better bonding performance and to remove excessive tannins. According to the results obtained, physical properties of laminated chestnut wood without tannin were better compared to samples with tannin. Oven-dry density and air-dry density were found to be higher in samples containing tannins and not exposed to thermal treatment. Moreover, the lowest value of density was observed in samples containing no tannin and exposed to thermal treatment. In terms of mechanical properties, the highest bending strength and modulus of elasticity were obtained from samples containing tannins and not exposed to heat treatment. The lowest values were found in samples without tannin exposed to heat treatment. Regarding compression strength, the maximum and minimum values were found in samples containing tannins and not exposed to heat treatment and samples without tannin and exposed to heat treatment, respectively.
Keywords: Anatolian Chestnut Wood; Laminated Wood; Pvac-D4; Mechanical Properties; Physical Properties